Optimal Parameters for Intervertebral Disk Resection Using Aqua-Plasma Beams - Yoon, Sung-Young; Kim, Gon-ho; Kim, Yushin; Kim, Nack Hwan; Lee, Sangheon; Kawai, Christina; Hong, Youngki (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Objective A minimally invasive procedure for intervertebral disk resection using plasma beams has been developed. Conventional parameters for the plasma procedure such as voltage and tip speed mainly rely on the surgeon's personal experience, without adequate evidence from experiments. Our objective was to determine the optimal parameters for plasma disk resection.Methods Rate of ablation was measured at different procedural tip speeds and voltages using porcine nucleus pulposi. The amount of heat formation during experimental conditions was also measured to evaluate the thermal safety of the plasma procedure.Results The ablation rate increased at slower procedural speeds and higher voltages. However, for thermal safety, the optimal parameters for plasma procedures with minimal tissue damage were an electrical output of 280 volts root-mean-square (Vrms) and a procedural tip speed of 2.5 mm/s.Conclusion Our findings provide useful information for an effective and safe plasma procedure for disk resection in a clinical setting.
Keywords: plasma ablation; disk herniation; minimally invasive procedure